String C-group representations of alternating groups - Fernandes, Maria Elisa (2019)
We prove that for any integer n ≥ 12, and for every r in the interval [3, . . . , Floor((n−1)/2)], the group A_n has a string C-group representation of rank r, and hence that the only alternating group whose set of such ranks is not an interval is A_11.